A Review of Authenticity and Authentication of Commercial Ginseng Herbal Medicines and Food Supplements - Ichim, Mihael Cristin; de Boer, Hugo J. (Frontiers in Pharmacology, 2021)
Ginseng traditional medicines and food supplements are the globally top selling herbal products. Panax ginseng, Panax quinquefolius and Panax notoginseng are the main commercial ginseng species in herbal medicine. Prices of ginseng products vary widely based on the species, quality, and purity of the used ginseng, and this provides a strong driver for intentional adulteration. Our systematic literature search has reviewed the authenticity results of 507 ginseng-containing commercial herbal products sold in 12 countries scattered across six continents. The analysis of the botanical and chemical identity of all these products shows that 76% are authentic while 24% were reported as adulterated. The number of commercial products as well as the percentage of adulteration varies significantly between continents, being highest in South America (100%) and Australia (75%), and lower in Europe (35%), North America (23%), Asia (21%) and Africa (0%). At a national level, from the five countries for which more than 10 products have been successfully authenticated, the highest percentage of adulterated ginseng products were purchased from Taiwan (49%), followed by Italy (37%), China (21%), and USA (12%), while all products bought in South Korea were reported to be authentic. In most cases, labeled Panax species were substituted with other Panax species, but substitution of ginseng root, the medicinally recommended plant part, with leaves, stems or flowers was also reported. Efficient and practical authentication using biomarkers to distinguish the main ginseng varieties and secondary metabolite spectra for age determination are essential to combat adulteration in the global marketplace.